2020
DOI: 10.1186/s12877-020-01894-0
|View full text |Cite
|
Sign up to set email alerts
|

Healthcare utilisation in the last year of life in internal medicine, young-old versus old-old

Abstract: Background With increasing cost of healthcare in our aging society, a consistent pain point is that of end-of-life care. It is particularly difficult to prognosticate in non-cancer patients, leading to more healthcare utilisation without improving quality of life. Additionally, older adults do not age homogenously. Hence, we seek to characterise healthcare utilisation in young-old and old-old at the end-of-life. Methods We conducted a single-site r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 42 publications
(39 reference statements)
5
14
0
Order By: Relevance
“…The FRAIL-NH scale was applied in studies across 20 countries; the majority in Australia (n=14) ( 21 34 ), followed by China (n=6) ( 35 40 ), Spain (n=3) ( 41 43 ), United States (US) (n=3) ( 44 46 ), Brazil (n=2) ( 47 , 48 ), Japan (n=2) ( 49 , 50 ), Singapore (n=2) ( 51 , 52 ), Belgium (n=1) ( 53 ), Canada (n=1) ( 54 ), England (n=1) ( 50 ), Europe and Israel (n=1) ( 55 ), France (n=1) ( 56 ), Hong Kong (n=1) ( 57 ), Italy (n=1) ( 58 ), South Korea (n=1) ( 59 ), and Taiwan (n=1) ( 60 ). One study was an international multicenter study based on data from the Services and Health for Elderly in Long TERm care (SHELTER) study, conducted in 8 countries including Czech Republic, England, Finland, France, Germany, Israel, Italy, and the Netherlands ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…The FRAIL-NH scale was applied in studies across 20 countries; the majority in Australia (n=14) ( 21 34 ), followed by China (n=6) ( 35 40 ), Spain (n=3) ( 41 43 ), United States (US) (n=3) ( 44 46 ), Brazil (n=2) ( 47 , 48 ), Japan (n=2) ( 49 , 50 ), Singapore (n=2) ( 51 , 52 ), Belgium (n=1) ( 53 ), Canada (n=1) ( 54 ), England (n=1) ( 50 ), Europe and Israel (n=1) ( 55 ), France (n=1) ( 56 ), Hong Kong (n=1) ( 57 ), Italy (n=1) ( 58 ), South Korea (n=1) ( 59 ), and Taiwan (n=1) ( 60 ). One study was an international multicenter study based on data from the Services and Health for Elderly in Long TERm care (SHELTER) study, conducted in 8 countries including Czech Republic, England, Finland, France, Germany, Israel, Italy, and the Netherlands ( 55 ).…”
Section: Resultsmentioning
confidence: 99%
“…Conversely, among non-users of statins, fall-related hospitalizations were lowest in the frailest subset ( 26 ). Five studies reported contrasting outcomes whereby FRAIL-NH scores did not predict falls ( 53 ), hospitalization ( 44 , 51 ), and mortality ( 41 , 53 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The United Nations (UN) predicted that there would be an average annual increase rate of 2.5% in the elderly population from 1990 to 2020, and over the same period, the proportion of the world's aging population has risen from 6.6% in 1995 to 9.3% in 2020 (1). Aging causes a decline in physical function, but also can induce a variety of diseases, such as diabetes, osteoarthritis, cataracts, and cancer (2).…”
Section: Introductionmentioning
confidence: 99%